2016
DOI: 10.1007/s00114-016-1342-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of the sex determination gene doublesex in a gynandromorph of bumblebee, Bombus ignitus

Abstract: Gynandromorphy that has both male and female features is known in many insect orders, including Hymenoptera. In most cases, however, only external morphology and behavioral aspects have been studied. We found a gynandromorph of bumblebee, Bombus ignitus, that showed almost bilateral distribution of external sexual traits, with male characters observed on the left side and female characters on the right side. This individual never exhibited sexual behavior toward new queens. The dissection of the head part show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In despite of this, the number of gynandromorphs for bees is still around 180 specimens (Wcislo et al, 2004;Michez et al, 2009;Fateryga et al, 2011;Hinojosa-Díaz et al, 2012;Lucia et al, 2012;Silveira et al, 2012;Camargo & Gonçalves, 2013;Lucia & Gonzalez, 2013;Alvarez et al, 2014;Lucia et al, 2015;Suzuki et al, 2015;Vivallo, 2015;Coelho et al, 2016;Ugajin et al, 2016), an underestimated number comparing to total number of described bee species nowadays, something around 20.000 (Danforth et al, 2013). As the majority of the records, gynanders of X. darwini and X. varipuncta were found in the museums collections, in dry preservation, and the descriptions were based only in external morphology (Bonnet, 1952;Carcasson, 1965;Lucia et al, 2009;Lucia et al, 2012;Camargo & Gonçalves, 2013;Lucia & Gonzalez, 2013;Alvarez et al, 2014;Lucia et al, 2015;Vivallo, 2015;Coelho et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In despite of this, the number of gynandromorphs for bees is still around 180 specimens (Wcislo et al, 2004;Michez et al, 2009;Fateryga et al, 2011;Hinojosa-Díaz et al, 2012;Lucia et al, 2012;Silveira et al, 2012;Camargo & Gonçalves, 2013;Lucia & Gonzalez, 2013;Alvarez et al, 2014;Lucia et al, 2015;Suzuki et al, 2015;Vivallo, 2015;Coelho et al, 2016;Ugajin et al, 2016), an underestimated number comparing to total number of described bee species nowadays, something around 20.000 (Danforth et al, 2013). As the majority of the records, gynanders of X. darwini and X. varipuncta were found in the museums collections, in dry preservation, and the descriptions were based only in external morphology (Bonnet, 1952;Carcasson, 1965;Lucia et al, 2009;Lucia et al, 2012;Camargo & Gonçalves, 2013;Lucia & Gonzalez, 2013;Alvarez et al, 2014;Lucia et al, 2015;Vivallo, 2015;Coelho et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As the majority of the records, gynanders of X. darwini and X. varipuncta were found in the museums collections, in dry preservation, and the descriptions were based only in external morphology (Bonnet, 1952;Carcasson, 1965;Lucia et al, 2009;Lucia et al, 2012;Camargo & Gonçalves, 2013;Lucia & Gonzalez, 2013;Alvarez et al, 2014;Lucia et al, 2015;Vivallo, 2015;Coelho et al, 2016). Just a few observations about biology and behavior of gynandromorphic forms have been made (Gordh & Gulmahamad, 1975;Wcislo et al, 2004;Michez et al, 2009;Giangarelli & Sofia, 2011;Hinojosa-Díaz et al, 2012;Silveira et al, 2012;Ugajin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon may offer insight into the evolution of specialized morphological traits, such as male-like morphology of female brood-parasitic bee lineages (Wcislo et al 2004a), the modified morphology of social insect castes (Yang and Abouheif 2011), and novel methods of reproduction (Aamidor et al 2018). Gynandromorphs are usually unnoticed until specimens are in museum collections, meaning that the behavior and physiology of these bees are seldom studied (Michez et al 2009, Sampson et al 2010, Ugajin et al 2016, Matsuo et al 2018). Here we report the first gynandromorph discovered in the bee species Megalopta amoena (Halictidae, Augochlorini); only one has been previously reported from the genus Megalopta (M. genalis Meade-Waldo, 1916;Wcislo et al 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…We tested the circadian rhythm of this individual using an automated activity monitoring system (Giannoni-Guzmán et al 2014). The few previous studies of live gynandromorphs have reported data on nesting behavior (Michez et al 2009), courtship (Michez et al 2009, Sampson et al 2010, Matsuo et al 2018, and gene expression (Ugajin et al 2016, Matsuo et al 2018. This is the first report of circadian activity monitoring in a gynandromorph.…”
Section: Introductionmentioning
confidence: 99%